2020
DOI: 10.1186/s12905-020-01038-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between levels of tumor-infiltrating lymphocytes in different subtypes of primary breast tumors and prognostic outcomes: a meta-analysis

Abstract: Background To investigate the impact of the elevation of tumor-infiltrating lymphocytes (TILs) in different molecular subtypes of primary breast cancer, i.e. each 10% increment of TILs and high-level TILs (TILs≥50%) in tumor, on overall survival (OS) and pathological complete response (pCR) and to compare the presentation of high-level TILs across these molecular subtypes. Methods Citation retrieval was performed in the PubMed, Cochr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
(39 reference statements)
3
21
0
Order By: Relevance
“…The achievement of pathological complete response (pCR) is a favorable prognostic factor for human epidermal growth factor receptor 2 (HER-2)-positive, triple-negative (TN), and high-grade hormone receptor (HR)-positive HER-2-negative breast cancers [ 10 ]. The presence and abundance of tumor-infiltrating lymphocytes (TILs) before NAC play crucial roles in the induction of therapeutic effects and favorable prognostic outcomes after chemotherapy for HER-2-positive and TN breast cancers [ 11 ]. After NAC, the activation of antitumor immunity through innate and adaptive immune responses, such as natural killer (NK) and CD8+ T cell activity, and the downregulation of immunosuppressive factors such as regulatory T cells (Tregs) and cytotoxic T lymphocyte antigen 4 within them, are important for the enhancement of the therapeutic effect [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The achievement of pathological complete response (pCR) is a favorable prognostic factor for human epidermal growth factor receptor 2 (HER-2)-positive, triple-negative (TN), and high-grade hormone receptor (HR)-positive HER-2-negative breast cancers [ 10 ]. The presence and abundance of tumor-infiltrating lymphocytes (TILs) before NAC play crucial roles in the induction of therapeutic effects and favorable prognostic outcomes after chemotherapy for HER-2-positive and TN breast cancers [ 11 ]. After NAC, the activation of antitumor immunity through innate and adaptive immune responses, such as natural killer (NK) and CD8+ T cell activity, and the downregulation of immunosuppressive factors such as regulatory T cells (Tregs) and cytotoxic T lymphocyte antigen 4 within them, are important for the enhancement of the therapeutic effect [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of multivariate analysis showed that any 10% increase in TIL density was associated with increase in overall survival and complete morphological response rates for all molecular subtypes. High TIL density (≥50%) leads to a 2.7fold increase in the complete response rates in TNB [54].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…However, this prognostic and predictive impact of the efficacy of chemotherapy depends on the breast cancer subtype, and is particularly marked in the triple negative and HER2 positive subtypes, in which there is more often a higher TMB, as well as greater inflammatory signature expression. Moreover, in the HER2 positive subtype, the immune response (in particular TIL levels) also seems to influence the effectiveness of anti-HER2 treatments, in particular monoclonal antibodies (possibly by the phenomenon of Antibody-Dependent Cell Cytotoxicity (ADCC)) [ 7 , 9 , 10 , 11 ]. Among TILs, the presence of CD8 + T cells, as well as the ratio between effector CD8 + and regulatory FoxP3 + T cells, appears to be associated with both better prognosis and long-term survival [ 7 , 12 , 13 ].…”
Section: Background and Current Development Of Immunotherapy With Anti-pd-1/pd-l1 In Breast Cancermentioning
confidence: 99%